The Effect of Service Quality and Sales Promotion on Consumer Loyalty at Ihsan Mart in Kubu Raya - Sukardi Sukardi; Fauziah Munawaroh; Muhammad Ebuziyya Alif Ramadhan (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the effect of service quality and sales promotion on consumer loyalty at Ihsan Mart in Kubu Raya. This study used an associative quantitative approach with 100 respondents selected through purposive sampling. Data were collected using questionnaires with a five-point Likert scale and analyzed using multiple linear regression with the assistance of SPSS. The results show that service quality and sales promotion have positive and significant effects on consumer loyalty, both partially and simultaneously. The regression results indicate that sales promotion has a greater contribution than service quality in increasing consumer loyalty. However, the coefficient of determination shows that service quality and sales promotion explain 16.3% of consumer loyalty, while the remaining 83.7% is influenced by other factors outside this study. These findings imply that local retail management should not only improve service quality and sales promotion programs, but also consider other factors such as customer satisfaction, product quality, price competitiveness, store atmosphere, and consumer trust to strengthen long-term consumer loyalty.